Middle Career Trap - Suwinto Johan (Universitas Tarumanagara, 2020)
The aim of the paper is to study the middle career trap for white collar worker. The research will be focused on the challenges which are faced by middle management. We will use the qualitative method on the analysis. The sample are 50 midlle managers who have more than 10 years working experience. The analysis will be faced to faced interview basis. The empirical results show that more than 10% of the middle managers are facing financial problem due to life style and family issues. There is a trap for the manager to improve their capabilities due to financial problem. The trap become a hurdle for the manager to promote to next level.